2017
DOI: 10.1093/rof/rfx022
|View full text |Cite
|
Sign up to set email alerts
|

Emotional State and Market Behavior

Abstract: We consider the relationship between the emotional state of traders and market prices. We create asset markets with the structure first studied by Smith, Suchanek and Williams (1988), which is known to generate price bubbles and crashes. We analyze participants' facial expressions with facereading software before and while the market is operating. We find that greater positive emotion in facial expressions before the market opens predicts higher prices and larger bubbles. Greater fear predicts lower prices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 48 publications
6
24
1
Order By: Relevance
“…We also conclude from the results in Tables 2-5 that hypothesis H1 is strongly supported by the data while H2, that negative emotional valence has a more substantial impact than positive valence, is refuted. Our base finding that risk tolerance increases with more positive emotional states and decreases with more negative ones is in line with several studies related to risk-taking tasks (e.g., Wright & Bower, 1992;Nygren et al, 1996;and Breaban & Noussair, 2018).…”
Section: Notesupporting
confidence: 93%
See 2 more Smart Citations
“…We also conclude from the results in Tables 2-5 that hypothesis H1 is strongly supported by the data while H2, that negative emotional valence has a more substantial impact than positive valence, is refuted. Our base finding that risk tolerance increases with more positive emotional states and decreases with more negative ones is in line with several studies related to risk-taking tasks (e.g., Wright & Bower, 1992;Nygren et al, 1996;and Breaban & Noussair, 2018).…”
Section: Notesupporting
confidence: 93%
“…Delis and Mylonidis (2015) find that happiness reduces the likelihood of purchasing risky assets, consistent with the mood maintenance hypothesis whereby investors are wary of taking on risk for fear of damaging their current good mood state. On the other hand, in a simulated trading experiment, Breaban and Noussair (2018) show that happiness is positively correlated with higher price levels of assets, confirming that its positive valence negatively relates to loss aversion.…”
Section: Methodology and Datamentioning
confidence: 97%
See 1 more Smart Citation
“…I then use a predictive regression to test whether emotions predict first-day returns. I take 1 The emotions in this paper correspond to the seven emotional states specified in Breaban and Noussair [2018]. For a detailed description of the classification schemes, see Vamossy and Skog [2023].…”
Section: Introductionmentioning
confidence: 99%
“…My study adds to the literature on behavioral finance by showing that firm-specific investor emotions on social media platforms can help explain IPO returns. Previous research has shown that emotions play a role in generating bubbles in experimental asset markets (e.g., Breaban and Noussair [2018], Andrade et al [2016]), traders' moods can lead to price movements at the market level (e.g., Kamstra et al [2003], Hirshleifer and Shumway [2003], Bollen et al [2011], Gilbert and Karahalios [2010]). However, I use direct proxies by measuring emotions in social media posts directly related to a stock listing.…”
Section: Introductionmentioning
confidence: 99%